The complete mitochondrial DNA of Gymnocypris potanini Herzensten and comparative mitogenomic analyses in Gymnocypris species. Issue 1 (1st January 2016) - Yan, Taiming; Hu, Jiaxiang; Cai, Yueping; Xiong, Sen; He, Zhide; Li, Song; Wang, Xiongyan; Yang, Deying; He, Zhi
Abstract: In the study, the complete mitochondrial genome of Gymnocypris potanini Herzensten was sequenced and compared with other Gymnocypris species. The mitochondrial genome, consisting of 16, 749 base pairs (bp), encoded 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a noncoding control region, similar as that found in other Gymnocypris species. These results can provide useful information for further studies on taxonomic status, molecular systematics, and stock evaluation.